2003
DOI: 10.1002/app.12925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrophilicity on the biodegradability of polyesteramides

Abstract: ABSTRACT:The effect of surface hydrophilicity was induced from the amide units in the polyesteramide. The surface energies and compositions of the polyesteramides were studied by employing contact angle and interfacial tension measurements and ESCA analysis. Biodegradability was evaluated form various methods including activated sludge test, enzyme hydrolysis, and soil burial test, which determine the amount of evolved CO 2 , weight loss, and TOC values, respectively. It was found that the introduction of amid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 8 publications
0
17
0
1
Order By: Relevance
“…The difference between the scaffolds containing 10% Tau and the other groups was statistically significant (p < 0.01) in both 30th and 60th days. The correlation between hydrophobicity and biodegradability can be attributed to the weight loss obtained results 29 . Since the hydrolysis is the main degradation mechanism of the prepared scaffolds, the incorporation of Tau enhanced weight loss through easier accessibility of water molecules to the polymer changes.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The difference between the scaffolds containing 10% Tau and the other groups was statistically significant (p < 0.01) in both 30th and 60th days. The correlation between hydrophobicity and biodegradability can be attributed to the weight loss obtained results 29 . Since the hydrolysis is the main degradation mechanism of the prepared scaffolds, the incorporation of Tau enhanced weight loss through easier accessibility of water molecules to the polymer changes.…”
Section: Resultsmentioning
confidence: 77%
“…Park et al 29 reported that there is a direct correlation between the hydrophilicity and biodegradability of polyesteramides scaffold. They also suggested that this correlation is through easier accessibility of water molecules to polymer chains.…”
Section: Resultsmentioning
confidence: 99%
“…For 30 days, we buried PVA/CS/DMC biodegradable films in the soil. According to the films' weight loss various time, the films' degradation curve can be calculated [32]. We buried the sample into the soil 10 cm away from the earth's surface.…”
Section: Biodegradability In Soilmentioning
confidence: 99%
“…Peroxidases and laccases are implicated in the degradation of PE, the former reducing the weight average molecular weight and the latter reducing the average molecular weight and average molecular number of the polymer [19,20]. Esterases and lipases are involved in degradation of polyester-type polymers [21,22]. A two-step action of bacterial extracellular hydrolases and of a combination of lipase, esterase, and protease activities was also reported in the degradation of the aliphatic-aromatic co-polyester Ecoflex ® [23,24].…”
Section: Introductionmentioning
confidence: 99%